Pemberdayaan Masyarakat melalui Pemanfaatan Susu Kambing dan Umbi Talas sebagai Sumberdaya Pangan Lokal untuk Mengatasi Stunting di Desa Genggelang Kabupaten Lombok Utara - Juniawan, Alvin; Wanadiatri, Halia; Swandayani, Rosalina Edy; Wedowati, Endang Retno; Rejeki, Fungki Sri; Haryanta, Dwi (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community service activity aims to empower the community by utilizing local food sources processed from taro tubers and Etawa goat's milk to overcome stunting in Genggelang Village, North Lombok Regency. The implementation method of this service included socialization, training, and mentoring. The evaluation instrument for this activity used a pre-test and post-test, which were then analyzed descriptively. The results of this service showed that the community increased knowledge and skills to process the potential of local village food into processed taro flour products, cookies, processed Etawa goat's milk products, and vegetable nuggets. The potential of these products could overcome the problem of stunting and improve the community's economy.